Efficiency Analysis of Healthcare Systems in Latin American and Caribbean Countries: An Application Based on Data Envelopment Analysis - Villalobos-Cid, M (Elsevier Inc., 2025)
Objectives: Despite the increasing investments in Latin American healthcare, the corresponding improvement in population health is not proportional. This discrepancy may be attributed to the efficiency of resource utilization. This study used the data envelopment analysis (DEA) methodology to assess the efficiency of healthcare systems in 23 Latin American and Caribbean countries. Methods: We used the most recent data from the World Bank (2017). Our analysis included healthcare expenditure (percentage of gross domestic product), hospital beds per 1000 inhabitants, physicians per 1000 inhabitants, and nurses per 1000 inhabitants as input variables. Life expectancy at birth and infant mortality rate were used as output variables. We conducted sensitivity analyses on model parameters to understand their influence. Linear and Tobit regressions were developed to comprehend the relationship between variables and DEA scores. Finally, we performed a temporal analysis of efficiencies to identify trends and patterns within the sample. Results: The DEA model classified 13 of the 23 analyzed countries as efficient, with 10 consistently maintaining this level throughout the 10 years of the temporal analysis: Belize, Chile, Colombia, Costa Rica, Cuba, Guatemala, Honduras, Jamaica, Mexico, and Peru. Conversely, 4 countries were never considered efficient: Barbados, Brazil, Nicaragua, and Uruguay. Conclusions: This study provides valuable insights for Latin American and Caribbean countries, offering a roadmap to manage their resources better and provide quality and equitable service to their people despite economic challenges. © 2024 International Society for Health Economics and Outcomes Research